The strength of neural entrainment to electronic music correlates with proxies of altered states of consciousness - Aparicio-Terrés, Raquel; López-Mochales, Samantha; Díaz-Andreu, Margarita; Escera, Carles (Frontiers in Human Neuroscience, 2025)
In electronic music events, the driving four-on-the-floor music appears pivotal for inducing altered states of consciousness (ASCs). While various physiological mechanisms link repetitive auditory stimuli to ASCs, entrainment—a brainwave synchronization through periodic external stimuli—has garnered primary focus. However, there are no studies systematically exploring the relationship between entrainment and ASCs. In the present study, we depart from the finding that entrainment to auditory stimuli peaks for stimulation rates around 2 Hz compared to others. Nineteen participants listened to six one-minute electronic music excerpts at different tempos (1.65 Hz, 2.25 Hz, and 2.85 Hz). For each excerpt, they performed cognitive tasks and reported phenomenological experiences related to ASCs through questionnaires. Brain activity was recorded with electroencephalography to assess whether a modulation in entrainment by the beat of electronic music affected objective and subjective proxies of ASCs. Our results revealed a tempo-driven modulation of entrainment at the group level, with entrainment being higher for stimulation rates at 1.65 Hz compared to 2.85 Hz. Similarly, music at 1.65 Hz aroused more feelings of unity compared to music at 2.85 Hz. However, at the individual level, no significant relationship was found between entrainment magnitude and phenomenological experience. Instead, a positive relationship was observed between entrainment and participants’ reaction time. The results suggest that brainwave entrainment modulate processes relevant to rhythm-induced ASCs. While we cannot determine whether participants entered an ASC due to design constraints, the observed relationship between entrainment and reaction time at the individual level supports its functional significance.